2016
DOI: 10.18553/jmcp.2016.22.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Care in Patients with Metastatic Renal Cell Carcinoma Among a U.S. Payer Population with Commercial or Medicare Advantage Membership

Abstract: Patterns of use were similar for each of the prescribed systemic treatments for mRCC, and the majority of patients were highly persistent and compliant with first-line therapies. Time to treatment discontinuation was slightly longer with oral agents compared with injectable drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
(21 reference statements)
1
19
0
Order By: Relevance
“…Reported results of real-world studies are mixed. For example, the observed sunitinib and sorafenib treatment durations were similar to those reported by Feinberg et al (5.9 and 5.5 months, respectively) [32] and only slightly longer than those reported by Miller et al (5.6 and 5.3 months, respectively), who also reported durations of 5.3 months for pazopanib and 4.5 months for everolimus [14]. However, these durations are slightly longer than those reported by Hess et al (3.2 and 4.0 months, respectively; 2.6 months for temsirolimus) [33] and Vogelzang et al (sunitinib, 4.1 months; pazopanib 4.8 months) [15].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Reported results of real-world studies are mixed. For example, the observed sunitinib and sorafenib treatment durations were similar to those reported by Feinberg et al (5.9 and 5.5 months, respectively) [32] and only slightly longer than those reported by Miller et al (5.6 and 5.3 months, respectively), who also reported durations of 5.3 months for pazopanib and 4.5 months for everolimus [14]. However, these durations are slightly longer than those reported by Hess et al (3.2 and 4.0 months, respectively; 2.6 months for temsirolimus) [33] and Vogelzang et al (sunitinib, 4.1 months; pazopanib 4.8 months) [15].…”
Section: Discussionsupporting
confidence: 84%
“…For 1 L treatment of clear cell RCC, current National Comprehensive Cancer Network (NCCN) guidelines recommend several treatment options with distinct mechanisms of action, including sunitinib or pazopanib as category 1 options [8]. Since the introduction of these agents, however, data on their use in routine clinical practice have been limited [1214] and have tended to focus on specific patient subgroups or selective treatments. With the changing landscape in the 1 L treatment of mRCC, an understanding of real-world treatment use, sequencing and associated adverse events (AEs) of historic but widely used and recommended current standard of care treatments is required [15, 16] and can provide practitioner, researcher and payer insights into the care and benefit:risk profiles of mRCC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Pathologic staging of RCC is essential for guiding clinical treatment decision-making process and selecting patients for potential adjuvant therapy (32). High-risk stage II and stage III RCC patients with clear cell histology are considered candidates for adjuvant therapy according to the National Comprehensive Cancer Network (NCCN) guidelines (33).…”
Section: Discussionmentioning
confidence: 99%
“…VEGFR-targeted therapies such as sunitinib and pazopanib have been the most commonly used first-line therapies in the United States over the past decade. [32] Sunitinib was shown in phase III study to confer improved overall survival (OS), progression-free survival (PFS), and objective response rate (ORR) as compared to interferon alfa in treatment-naïve patients with clear cell mRCC. [16] Later, the randomized phase III COMPARZ trial demonstrated pazopanib to be non-inferior to sunitinib in OS and PFS,[18,19] and both COMPARZ and a separate randomized phase IIIb study (PISCES trial) suggested pazopanib to be better tolerated than sunitinib.…”
Section: Overview Of the Marketmentioning
confidence: 99%